Pc 3 magnetic pulsations observed at low latitudes: A possible model - Yumoto,Kiyohumi; Saito,Takao; Tanaka,Yoshihito (1987)
P(論文) It is recently demonstrated that Pc 3 magnetic polarizations observed at equatorial latitudes (|φ|<20°) are different from those at low-latitude Japan-Australia conjugate stations (|φ|∿35°). In order to interpret the Pc 3 polarization characteristics at lower latitudes (|φ|≲45°), we propose a probable, new qualitative model in which two (or more) superimposed ionospheric eddy currents, oscillating with slight differences in frequency in the Pc 3 range and in apparent azimuthal wave number, move azimuthally at low latitudes (|φ|≲45°). Near low latitudes of |φ|∿45°ionospheric rotational Hall currents should be induced by field-aligned currents associated with localized shear Alfven waves which are excited by compressional Pc 3 source waves near |φ|∿45°. Near the equatorial region ionospheric Pedersen eddy currents may be caused by inductive electric fields of compressional Pc 3 source waves which would propagate from the outer magnetosphere to the equatorial ionosphere. departmental bulletin paper